Faktor Penentu Kesuksesan Web-Based Appointment System di Rumah Sakit - Taufan Halim; Gede Sri Darma (Jurnal Manajemen dan Bisnis, 2019)
ABSTRACTWeb-based appointment system (WAS) is one of digital strategy in hospital industry. It promising benefits in reducing waiting time, reducing no show rate and increasing patient’s satisfaction. This competitive advantage not fully obtained because this method not fully accepted in patient’s side. The aim of this study is exploring the factor that affecting patient’s acceptance on WAS in hospital. This study uses a qualitative method that explores the acceptance of patient on WAS by using technology acceptance model approach. Siloam Hospital Bali was selected as the place of study since this hospital is the only hospital in Bali that use WAS and linked directly to their hospital information system. Six informants were selected using purposive, accidental and saturation sampling, divided into 3 informants who were using WAS and 3 informants who were not. Observation and in-depth interview were conducted during this study. Data is then analyzed qualitatively by data reduction, display and conclusion drawing. Data verification was performed by triangulation technic. The study shows perceived usefulness (PU) and ease of use (PEU) is the main factor that determining patient’s acceptance on WAS. Three factors are identified affecting the PU and PEU. This factor are user experience, web/application and hospital responsiveness. The study shows lack of information of WAS existence is the main reason for not using it. We recommend special concern to this factor before implementing WAS. By identifying and concerning to this factor, implementation of this system will bring competitive advantage to the hospital.